2018
DOI: 10.12659/ajcr.907251
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Recurrent Pasteurella Bacteremia in an Immunocompetent Patient with No Animal Bite

Abstract: Patient: Male, 61Final Diagnosis: Recurrent pasteurella bacteremiaSymptoms: Ankle painMedication: —Clinical Procedure: —Specialty: Infectious DiseasesObjective:Rare diseaseBackground:Pasteurella multocida is a gram negative-penicillin sensitive bacterium and is part of normal respiratory microbiota of animals (e.g., cats and dogs) and some birds. Various infections in humans, such as cellulitis, rarely bacteremia, endocarditis, meningitis, and septic arthritis, are a result of domestic cat or dog bites. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Infrequent and unlikely complications such as meningitis, endocarditis, and septic arthritis have also been associated with P. multocida [ 6 , 7 ]. A case study by Clarke et al, treated a patient who presented with symptoms consistent with meningitis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infrequent and unlikely complications such as meningitis, endocarditis, and septic arthritis have also been associated with P. multocida [ 6 , 7 ]. A case study by Clarke et al, treated a patient who presented with symptoms consistent with meningitis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, a history of multiple prosthetic joints significantly elevated the risks associated with bacteremia due to her increased susceptibility to joint seeding. While most documented cases of Pasteurella bacteremia are in patients who suffered animal bites and scratches, there are documented cases in which the source of the infection was considered to be licking of an existing wound or kissing of the animal [ 3 , 4 , 13 ]. Of significant interest is the fact that the patient was taking lenalidomide at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the hypothesis that the licking of an already existing wound led to infection with P. multocida , the patient has multiple dogs and cats and reported that one cat has a tendency to lick people and objects. Cases in which licking was considered to be a likely mode of transmission have been documented [ 4 , 62 ]. Additionally, one retrospective review noted that cases of P. multocida bacteremia where animal bites were not noted as the inciting event for infection were found to have poorer outcomes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] While immunocompromised patients have a higher rate of systemic infection and mortality, they are less likely to present with evidence of a bite wound. [1,4,5] We present a case of Pasteurella multocida bacteremia causing the death of an 80-year old immunocompromised female. While oropharyngeal colonization was the clinically suspected route of entry, a bite wound was ultimately discovered at autopsy.…”
Section: Introductionmentioning
confidence: 99%